Constructing political expertise in the news - Searles, Kathleen ca. 20./21. Jh; Krupnikov, Yanna ca. 20./21. Jh; Ryan, John Barry 1979-; Style, Hillary ca. 20./21. Jh (Cambridge elements, 2023)
This work considers patterns in expert sources, focusing on politics. Jointly, the results of the survey suggest underlying patterns in expert sourcing is a tension between journalists' preferences, the time constraints of producing news, and the preferences of the experts themselves